2018
DOI: 10.1039/c8nj01395k
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of carbohydrate fused pyrano[3,2-c]pyranones as anticancer agents

Abstract: Efficient synthesis of pyrano[3,2-c]pyranones motif as fused carbohybrids and their anticancer activities reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The results showed that most of carbohydrate fused compounds inhibited growth of parasite in vitro (Additional file 1: Table S1). These compounds exhibited no cytotoxicity even at higher concentration of 100 µM against HepG2 cells (liver hepatocellular carcinoma) as described in the previous work [8].…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…The results showed that most of carbohydrate fused compounds inhibited growth of parasite in vitro (Additional file 1: Table S1). These compounds exhibited no cytotoxicity even at higher concentration of 100 µM against HepG2 cells (liver hepatocellular carcinoma) as described in the previous work [8].…”
Section: Resultssupporting
confidence: 55%
“…This indicates that this compound is efficient against both the chloroquine sensitive and the resistant strains. Upon structural analysis of this compound as depicted by structure activity relationship (SAR) studies, carbohybrid 12 has 2-OMe group at C-2 position which might be playing an important role for its anti-malarial activity [8]. To assess whether the inhibitory potential of carbohybrid 12 is not due to haemolytic effect of compound itself, uninfected erythrocytes were incubated with different concentrations of compound (1–50 μM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations